Supratentorial malignant ependymoma in childhood: 16 years without relapse after hemispherectomy - Ahmadi, Rezvan; Schmitt, Horst Peter; Kunze, Stefan; Steiner, Hans H. (Child's nervous system, 2005)
IntroductionMalignant intracranial ependymomas in childhood have a poor prognosis, supratentorial ependymomas have the poorest clinical course with a survival rate after 5 years of 45%. The most important prognostic factor in these cases is a radical operation, which cannot usually, however, prevent relapse.Case reportWe demonstrate the case of a large malignant ependymoma of the left cerebral hemisphere in a child who has so far lived for 16 years without relapse after an extensive but uncomplicated left-sided hemispherectomy. The patient has also shown an improvement in her preoperative neurologic deficits. Her epilepsy, which was difficult to manage preoperatively, has been completely eliminated. She went to a special school for handicapped children and now works there. She does not need any help in handling everyday activities.Conclusion This case shows the significance of complete tumor resection in malignant ependymomas, which may, under certain circumstances, lead to lasting tumor control.